Depression and Cognitive Impairment among the Elderly in Rural and Urban Areas of Shimoga - Nandini C; Sridevi NH (Medsci Publications, 2019)
Background: Elderly people suffer from communicable and non-communicable diseases. This is compounded by impairment of sensory functions like vision, hearing, and stability management leading to cognitive impairment. Elder mistreatment, financial exploitation, psychological abuse and abandonment may have serious medical and social consequences like depression Objective: The study was conducted to assess the burden of depression and cognitive impairment among the elderly persons in a rural and urban field practice areas of Shimoga Institute of Medical sciences, Shimoga. Methods: A cross sectional study was conducted among elderly in rural and urban field practice areas of Shimoga Institute of Medical Sciences, Shivamogga. Data was collected by doing house-to-house visits after informed consent with semi-structured, pre-designed and pre-tested questionnaire. Analysis was done by using SPSS version 21 software. Proportions and frequencies were calculated, the Chi Square statistical test was used to analyze the association between variables. Conclusion: The study concluded that the prevalence of depression in rural elderly was established to be 60/210(28.6%) while in urban elderly it was 85/210(40.5%). Based on MMSE for assessing cognitive impairment showed 20% (42), 2.9% (6) had mild and moderate impairment respectively in rural areas where as in urban 38.1%(80), 14.3%(30) had mild and moderate impairment respectively.